Psichological disposition of student; Mathematics anxiety vesus happines learning on the level education - Widodo Winarso; Arif Abdul Haqq (SAINTIS Publishing, 2019)
The purpose of this study is to analyze students' psychological dispositions about student learning anxiety and happiness on the level of education. Elementary school, Junior high school and Senior High School students in the city of Cirebon were the subjects in this study. Mixed methods research with a sequential transformative strategy model was chosen to answer the problem of this research. Through a stratified random sampling technique, two types of research data were obtained; quantitative and qualitative data. Both of these data were analyzed by two data analysis techniques. Quantitative data analysis used is chi-square and contingency correlation, while qualitative data analysis uses triangulation of data sources. The results showed that there were differences in the level of mathematics anxiety and learning happiness of students at each level of education. Senior High School students have a high level of math anxiety when compared to elementary and Junior high school students. While in terms of happiness learn, students the elementary school is happier learning when compared to the other two types of students. This condition is also strengthened by the existence of a significant relationship between mathematics anxiety and happiness learn student with the level of education